The use of macro-rules reading comprehension of expository texts - Julcamayan Chagua, Cintya Estefani (2019)
This research focuses on answering the question, how does the use of macro-rules affect the understanding of expository texts? The population consisted of 190 students of the second grade of secondary school from the 1190 Educational Institution in Chosica. A questionnaire and a test were designed and applied, using a correlational-causal design, to 180 students, through a census that excluded some of them who had irregular attendance. The results show that the use of macro-rules affects the levels of literal, inferential and critical understanding of expository texts. Therefore, it is concluded that the use of macro-rules affects the understanding of expository texts (p <0.01; r = 0.317 which is considered a weak correlation and 10.1 % influence).